Chemokines in progression, chemoresistance, diagnosis, and prognosis of colorectal cancer - Zou, Qian; Lei, Xue; Xu, Aijing; Li, Ziqi; He, Qinglian; Huang, Xiujuan; Xu, Guangxian; Tian, Faqing; Ding, Yuanlin; Zhu, Wei (Frontiers in Immunology, 2022)
Plenty of factors affect the oncogenesis and progression of colorectal cancer in the tumor microenvironment, including various immune cells, stromal cells, cytokines, and other factors. Chemokine is a member of the cytokine superfamily. It is an indispensable component in the tumor microenvironment. Chemokines play an antitumor or pro-tumor role by recruitment or polarization of recruiting immune cells. Meanwhile, chemokines, as signal molecules, participate in the formation of a cross talk among signaling pathways and non-coding RNAs, which may be involved in promoting tumor progression. In addition, they also function in immune escape. Chemokines are related to drug resistance of tumor cells and may even provide reference for the diagnosis, therapy, and prognosis of patients with colorectal cancer.